Paracoccidioides brasiliensis antigen batches from the same isolate show immunological and biochemical differences - Franco, Marcello [UNESP]; Bagagli, Eduardo; Cunha, Marino; Chamma, Luiz Gastão; Fecchio, Denise [UNESP] (My University, 1996)
We investigated the occurrence of antigenic and biochemical variability among Paracoccidioides brasiliensis antigen batches prepared according to the same protocol. Initially (experiment 1), we analyzed two antigen lots of two human isolates (Bt1 and Bt2), cultured in two media (PYG: bactopeptone, yeast extract, glucose; MMM: McVeigh and Morton medium) in SDS-PAGE and in two immunological tests (immunodiffusion-ID and footpad swelling test-FPT). Afterwards (experiment 2), we compared the antigenic profile of three antigen hatches from three human isolates (Bt1, Bt2 and Bt3) by two-dimensional immunoelectrophoresis (2 D-IEP) against a reference system for P. brasiliensis antigens. In experiment 1, there were important intra- and inter-strain antigenic differences between batches of the fungal isolates cultured on both media. The block titration of the antigen batches for the immunological tests revealed correlation between protein concentration and biological activity in ID and no correlation in FPT. In experiment 2, the reference system for P brasiliensis showed 26 antigen peaks. There were important differences between batches prepared from the same isolate and between batches from different isolates. Our data suggested the occurrence of instability in the synthesis of antigenic components by a same P. brasiliensis isolate, under controlled incubation conditions.
Keywords: fungal antigen; Paracoccidioides brasiliensis; Paracoccidioidomycosis; fungal protein; fungus antigen; crossed immunoelectrophoresis; culture medium; genetic variability; human; immunodiffusion; immunology; metabolism; microbiological examination; microbiology; Paracoccidioides; polyacrylamide gel electrophoresis; South American blastomycosis; Antigens, Fungal; Bacteriological Techniques; Culture Media; Electrophoresis, Polyacrylamide Gel; Fungal Proteins; Humans; Immunodiffusion; Immunoelectrophoresis, Two-Dimensional; Variation (Genetics); Fungi